Meeting Points between Hypnotherapy and Music Therapy - Vas, Jozsef Pal; Csaszar-Nagy, Noemi (New Horizons in Medicine and Medical Research Vol. 12, 2022)
Sound vibrations are viewed to play an important role in embryonic development. Before cochlea has been evolved haptic and mechanic skin-receptors detect amniotic fluid’s pressure-waves produced by sounds in uterus. Touching and hearing are seen as primordial and the most relevant stimuli both of mother-fetus attunement and development of fetal nervous system. Man is attuned to environmental stimuli, mainly to human speaking since embryonic period. Attunement is maintained through energy zones (chakras) that round the body. It is thought to be the foundation of our musical ability. Our hypnotic susceptibility is thought to have started during the embryonic era. Movements, experiences supposed, bonding and communication patterns of both of fetus and hypnotized person are suggested to show similarities. Prenatal audio-somatosensory stimulating program facilitates newborn babies’ cognitive, emotional and bonding capacities. Nevertheless, hypnotherapy contributes to re-starting development of personality halted by trauma by virtue of regressive fetal-like experiences.